Do Both Intrinsic and Identified Motivations Have Long-Term Effects?. Issue 3 (3rd April 2019) - Liu, Yuan; Hau, Kit-Tai; Zheng, Xin
Abstract: This research examined the possible long-term effects of autonomous motivation on educational outcomes in the large scale High School Longitudinal Study 2009 (HSLS:09) data. We used a three-wave cross-lagged model to examine the longitudinal effects of intrinsic and identified motivation on 18, 132 students in the mathematics domain and 16, 684 students in the science domain. The results showed that intrinsic motivation was a long-term and effective enhancement agent on the subsequent academic performance, self-efficacy, identity, and course effort. In contrast, identified motivation might be sensitive to the contexts and was thus vulnerable to change in the long-term effects. Though identified motivation has positive effects on some immediate educational outcomes and is often regarded as "helpful" motivation, its positive effect is probably short-lived and might not last long in real life educational settings.